New insights and access to resources change the perspective on life among persons with long‐term illness-An interview study - Åsa Hedlund; Tina Nordström; Marja‐Leena Kristofferzon; Annika Nilsson (Wiley, 2019)
Abstract Aim The aim was to describe individuals' experiences of living with long‐term illness. Methods A qualitative approach with a descriptive design was used. Semi‐structured interviews were conducted with 16 persons (50-80 years). They were also asked to self‐rate their perceptions of their current health status and confidence in their ability to cope with everyday life. Results One main theme was identified: new insights and access to resources change the perspective on life. Personal characteristics and support from others were advantageous in finding ways to deal with limitations related to the illness. Most of the persons experienced a changed approach to life, in that they now valued life more than they had before. However, some persons also experienced lost values and found it difficult to accept medications. The persons rated their current health status as slightly above average, but their confidence in their ability to cope with everyday life as high.